2002
DOI: 10.1021/ja0282588
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Asymmetric Grignard Cross-Coupling of Dinaphthothiophene Giving Axially Chiral 1,1‘-Binaphthyls

Abstract: Asymmetric cross-coupling of dinaphtho[2,1-b:1',2'-d]thiophene with ArMgBr (Ar = Ph, 4-MeC6H4, 4-MeOC6H4) proceeded with high enantioselectivity in THF at 20 degrees C in the presence of 3 mol % of a nickel catalyst generated from Ni(cod)2 and a chiral oxazoline-phosphine ligand to give high yields of axially chiral 2-mercapto-2'-aryl-1,1'-binaphthyls, whose enantiomeric excesses are over 93%. The mercapto group in the chiral binaphthyl was converted into iodo, boryl, and phosphino groups without racemization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(66 citation statements)
references
References 27 publications
0
66
0
Order By: Relevance
“…Pioneering work by Hayashi 6,182 has shown that the axially chiral biaryls can be synthesized in high enantioselectivity by a Pd-catalyzed asymmetric Kumada coupling using chiral phosphine ligands (eqs 145 and 146). Thus, a selective substitution of one of the two triflate groups of achiral biaryl triflate 476 by either aryl or alkynyl Grignard reagents in the presence of chiral phosphine ligands 479a-c yielded axially chiral biaryls 477 in high yields and ee's (Table 16, entries 1-4).…”
Section: Kumada-type Cross-couplingsmentioning
confidence: 99%
“…Pioneering work by Hayashi 6,182 has shown that the axially chiral biaryls can be synthesized in high enantioselectivity by a Pd-catalyzed asymmetric Kumada coupling using chiral phosphine ligands (eqs 145 and 146). Thus, a selective substitution of one of the two triflate groups of achiral biaryl triflate 476 by either aryl or alkynyl Grignard reagents in the presence of chiral phosphine ligands 479a-c yielded axially chiral biaryls 477 in high yields and ee's (Table 16, entries 1-4).…”
Section: Kumada-type Cross-couplingsmentioning
confidence: 99%
“…The orange Ti IV complex 3 derived from 2, (i-PrO) 4 Ti, and 3,5-di-(tert-butyl)salicylic acid catalyzes (2 mol-%) the acetate aldol addition of O-trimethylsilyl O-methyl ketene acetal and aldehydes in good yields and high levels of asymmetric induction (Scheme). The Ti IV complex in this catalytic process displays some unique features relative to other Ti IV complexes that have been reported to date pertaining to its wide substrate scope [8].…”
mentioning
confidence: 99%
“…Dinaphthothiophenes (DNTs) are a class of compounds structurally similar to thiophene‐based organic semiconductors and have shown promise for use in p‐type organic semiconductors . DNTs have also been used as precursors to axially chiral 1,1′‐binaphthyl catalysts, which play a large role in asymmetric synthesis . In addition, dibenzothiophene S‐oxide (DBTO) and its derivatives are a class of compounds suggested to release O( 3 P) upon irradiation with UV light .…”
Section: Introductionmentioning
confidence: 99%